Penatalaksanaan Penyinaran Radioterapi Eksterna Pada Kanker Vagina Menggunakan Teknik Intensity Modulated Radiation Therapy (IMRT) Di Cancer Center Radioterapi Santosa Hospital Bandung Kopo - Mohd Alimin; Ni Putu Rita Jeniyanti; Leni Sri Wahyuni (Jurnal Ventilator, 2023)
Management Of External Radiotherapy Irradiation In Vaginal Cancer Using Intensity Modulated Radiation Therapy (IMRT) Technique At The Cancer Center Radiotherapy Santosa Hospital Bandung Kopo. Vaginal carcinoma constitutes approximately 2% of all malignant neoplasms that occur in the female genital tract. Vaginal carcinoma can arise from various types of cells within the vaginal wall and is often associated with risk factors such as exposure to certain carcinogens (8). Cancer is one of the main causes of death throughout the world. Based on GLOBOCAN data, the International Agency for Research on Cancer (IARC) in 2018, deaths caused by cancer reached around 9.5 million people, with 60% of cancer deaths in Asia. (7) Radiotherapy is a cancer treatment approach that uses light. ionizer to damage tumor cells while maintaining the integrity of surrounding healthy tissue. The main focus is to eliminate as many cancer cells as possible while reducing the negative impact on normal tissue around the tumor area. (20) There are several treatments for patients suffering from vaginal cancer, namely surgery, radiation, brachytherapy, and external radiation based on the size and stage of the tumor suffered by the patient. (3) Based on the book "Target Volume Dileniation And Filed Setup" (a practical guide for conformal and Intensity-Modulated Radioation Therapy), Arno.J, (2013: 201), all vaginal cancer patients who undergo radiation using the IMRT technique must simulated in a supine position and the patient's legs straight with a thermoplastic immobilization mask and adjusted immobilization of the upper and lower body (16).